Sinkretisme Agama dan Budaya Bagi Masyarakat Jawa - Ghozali, Achmad (Javano Islamicus, 2023)
This article discusses the relationship between religion and culture within Javanese society, emphasizing that both are closely interconnected. Parents play a significant role in educating their children to remain steadfast in upholding religious and cultural values. The purpose of this study is to explore the interrelation between religion and culture among the Javanese people. This research employs a library research method by analyzing relevant literature and previous studies. The findings reveal that Javanese society possesses a profound understanding of the inseparable bond between religion and culture, perceiving them as an integrated unity rather than distinct entities. Consequently, religion is not viewed as something apart from their cultural identity. Instead, both religion and Javanese culture jointly shape the ethics, norms, and behavioral patterns characteristic of their community. This integration demonstrates the vital role of religion and culture in constructing the moral foundation and daily life of the Javanese people.